RARE EARTH ELEMENTS IN MINERALS, ORES, AND ROCKS FROM URANIUM DEPOSITS OF NORTHERN KAZAKHSTAN: DISTRIBUTION AND GENETIC IMPLICATION - Vinokurov S.F.; Krylova T.L.; Timofeev A.V.; Golubev V.N. (My University, 2004)
REE distribution was studied in rocks, ores, and minerals from uranium deposits of Northern Kazakhstan. In terms of the style of premineral metasomatic alteration, mineralogic composition, and order of mineral formation, the deposits are subdivided into two genetic groups, beresitic and aceitic. REE distribution was considered using a special method in combination with data on thermobarogeochemistry, isotopic geochronology, and electron microscopy. It was found that the REE distribution patterns for hydrothermally altered rocks, as well as gangue and ore minerals, from the uranium deposits of the above groups are different, indicating different sources of the mineralizing hydrothermal fluids. Deposits of the beresitic group could be derived from an upper-crustal granite source; while those of the aceitic group, from a deeper seated lower-crustal to upper-mantle source. Strong changes in REE distribution in pitchblendes from the Vostok deposit under the effect of postore fluids should be taken into account during analysis of REE behavior in uranium ores. It was found that some postore carbonates and Permian-Triassic basalts have comparable REE distribution patterns. Geological, geochemical, and isotopic-geochronological data show that the fluids which transformed primary uranium ores and caused precipitation of some part of postore carbonate could be related to the platformal activation of Northern Kazakhstan.